KONTRAK PEMBIAYAAN MURABAHAH DAN MUSAWAMAH - Ilyas, Rahmat (Universitas Islam Negeri Sunan Kudus, 2015)
Islamic bank is a financial intermediary (Intermediary Financial Institution) whose operations are free from elements that are forbidden by Islam, namely gambling, Gharar, Riba, Ryswah, and falsehood.Thus different from conventional banks whose. operations using the principles of interest by most scholars say the same as usury. The element that distinguishes Islamic bank with a conventional bank is the necessity of Shariah Supervisory Board (DPS) under the auspices of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). Shariah Supervisory Board (DPS) is to monitor the operation of the bank and the products it releases in order to remain in accordance with the provisions of Shari’ah. Murabaha is a contract of sale of goods by the price of the goods plus an agreed profit margin. Based on the bank’s sale and purchase agreement to buy the goods ordered by and sold to customers. Bank selling price is the purchase price of the supplier plus an agreed profit.